Penerapan Model Project Based Learning Untuk Meningkatkan Motivasi Belajar Peserta Didik Kelas III Sekolah Dasar SDN 26 Cakranegara - Nurdina, Nurdina; Solihin, Solihin; Aminundin, Aminundin (Journal of Science Instruction and Technology, 2023)
This research aims to obtain information on the extent to which student motivation and learning outcomes increase by implementing the project-based learning model. The problem formulation in this research is "How the application of project-based learning can increase the motivation and learning outcomes of class III A students at SDN 26 Cakranegara" This type of research is Collaborative Classroom Action Research (PTK) in collaboration with DPL, tutor teachers, class teachers and friends’ colleague. The subjects in this research were 35 students in class III A of SD Negeri 26 Cakranegara, consisting of 19 male students and 16 female students. The data collection techniques used in this research are observation techniques and learning outcomes carried out during the ongoing implementation of PPL in cycle I and cycle II. The data analysis techniques used are quantitative and qualitative techniques. Quantitative techniques for processing quantitative data from test results. Meanwhile, qualitative techniques are used to analyze non-test qualitative data. Based on research conducted by researchers, it can be concluded that the application of the Project Based Learning model in class III A of SDN 26 Cakranegara has proven effective in increasing student motivation and learning outcomes. The research results showed that learning motivation reached 55% in the pre-cycle, 65% in cycle 1 and increased to 90% in cycle II. Based on these results, there was an increase of up to 35% and has exceeded the previously determined percentage of 80%. Meanwhile, in terms of student learning outcomes, there has been an increase in the number of students who have completed thematic subjects. In pre-cycle to cycle II the increase reached 46% with an average score reaching 80 and exceeding the KKM determined by the school. Thus, the use of the Project Based Learning model is effective in increasing the motivation and learning outcomes of class III A students at SDN 26 Cakranegara for the 2022/2023 academic year.